Decoding the Secrets of Agricultural Light, Heat, and Water Resources in Beijing Under Climate Change: Spatio-Temporal Variations on a Small Scale and Future Prospects - Hongrun Liu; Yanan Tian; He Zhao; Song Liu; Ning Zhu; Yanfang Wang; Wei Li; Dan Sun; Tianqun Wang; Lifeng Li; Shangjun Wu; Fudong Wang; et al. (Agriculture)
As an international metropolis, Beijing still plays a key role in the development of national agricultural production technology despite its small regional scale. Climate change has a great impact on agricultural production. Previous studies often focus on a single short-term meteorological factor and lack a more systematic analysis of climate resources in Beijing. Based on the daily temperature, precipitation, relative humidity, wind speed and sunshine hours of 17 meteorological stations in Beijing in the past 42 years, this study analyzed the spatial and temporal distribution characteristics of agro-climatic resources and predicted the future climate change trend under different climate scenarios. The climate resource tendency rate is calculated on a time scale of every ten years (10a). The results showed that (1) the light resources are decreasing at a rate of 44.9~156.3 MJ m−2 10 a−1, and the downward trends in light resources in the northeastern plain areas as well as in June and July are more significant; (2) the thermal resources are increasing at a rate of 34.2~176.4 °C·d 10 a−1, and the upward trends in thermal resources in the southeastern plain areas and in March are more remarkable; (3) the water resources represented by the soil humidity index are changing at a rate of −1.6~6.1% 10 a−1. The situation is complex, and the fluctuations of water resources in the central and western regions as well as in July, August and September are more significant; and (4) compared with the low-emission “dual carbon” scenario, the decrease in water volume and the overall increase in temperature in the high-carbon scenario are larger, and this trend is particularly obvious in the long run. This study provides a basis for Beijing’s agricultural layout and response to climate change, and its methods and results are also valuable for other regions to promote green, high-quality and sustainable agricultural development.